Study of the genus Meleonoma Meyrick, 1914 (Lepidoptera: Autostichidae) from China (III), with descriptions of eighteen new species - Wang, Shuxia; Zhu, Xiaoju; Tao, Zhulin (Zootaxa, 2021)
Eighteen new species of the genus Meleonoma Meyrick are described: M. arcivalvata sp. nov., M. chongqingensis sp. nov., M. curvativa sp. nov., M. curvitaeniana sp. nov., M. dilatifasciata sp. nov., M. fasciptera sp. nov., M. globoidea sp. nov., M. graciliclavata sp. nov., M. grandivalvula sp. nov., M. lunata sp. nov., M. medispinea sp. nov., M. proapicalis sp. nov., M. raphidacantha sp. nov., M. sinuaclavata sp. nov., M. tenuiclavata sp. nov., M. tetrodonta sp. nov. M. ventridentata sp. nov. and M. ventrisinuata sp. nov. The female of M. similifloralis (Wang, 2006) is described for the first time. Images of both adults and genitalia are provided. All species are divided into two species-groups, the dentivalvata species-group and the fasciptera species-group. A key to each group and maps showing the distribution of each group in China are given.